A Systematic Review of the Needs of Dementia Caregivers Across Care Settings. Issue 2 (May 2022) - Mueller, Anne; Thao, Lesley; Condon, Olivia; Liebzeit, Daniel; Fields, Beth
The U.S. population of older adults living with dementia is projected to double by 2060. They rely on over 16 million family and unpaid caregivers to provide for their increasingly complex needs and care transitions. Caregivers frequently feel underprepared and without adequate support or access to resources. This systematic review seeks to identify the needs of family and unpaid caregivers of older adults living with dementia across various care settings in the U.S. A systematic search was conducted to identify articles pertaining to the needs of caregivers of older adults living with dementia. The data extraction tool was developed using aspects from the Care Transitions Framework and the Family Caregiver Alliance. Data were organized based on 3 domains of caregiver needs and the care setting(s) of the older adults living with dementia and their caregivers. A total of 31 articles were eligible for inclusion. The majority met the MMAT screening criteria, but more than half only met 2 or less of the 5 quality criteria. Caregivers' needs were identified in the care settings of home/community-residing, assisted living, long-term care, skilled nursing, and memory care. Most articles either did not specify a care setting or included more than 1 and did not report the findings separately. Caregivers in each care setting, except memory care, identified needs in all 3 of the following domains: (1) social support—formal and informal, (2) confidence, competence, and strengths in the caregiving role, and (3) values and preferences.